Pyroxene‐type compounds NaM3+Ge2O6, with M = Ga, Mn, Sc and In. Issue 9 (7th August 2014) - Redhammer, Günther J.; Tippelt, Gerold
<x xml:space="preserve">Abstract</x> The four title compounds, namely sodium gallium germanate, NaGaGe2O6, sodium manganese vanadate germanate, NaMnV0.1Ge1.9O6, sodium scandium germanate, NaScGe2O6, and sodium indium germanate, NaInGe2O6, adopt the high‐temperature structure of the pyroxene‐type chain germanates, with monoclinic symmetry and space group C2/c. The lattice parameters, the individual and average bond lengths involving M1, and the distortion parameters scale well with the ionic radius of the M1 cation. NaGaGe2O6 has more distorted M1 sites and more extended tetrahedral chains than NaInGe2O6, in which a high degree of kinking is required to maintain the connection between the octahedral and tetrahedral building units of the pyroxene structure. An exceptional case is NaMnGe2O6, in which the strong Jahn–Teller effect of Mn3+ results in more distorted octahedral sites than expected according to linear extrapolation from the other NaM3+Ge2O6 pyroxenes. In contrast with the literature, minor incorporations of V5+ in the tetrahedral site and a corresponding reduction of Mn3+ to Mn2+ in the octahedral sites in the present sample lower the Jahn–Teller distortion and stabilize the Mn‐bearing pyroxene, even allowing its synthesis at ambient pressure.